2021
DOI: 10.3390/biomedicines9050561
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in Follicular Lymphoma Staged by 18F-FDG-PET/CT: A German Monocenter Study

Abstract: This retrospective study examined the role of 18F-fluorodeoxyglucose-positron emission tomography/computed tomography (18F-FDG-PET/CT) in stage-related therapy of follicular lymphomas (FL). Twelve patients each in stages I and II, 13 in stage III and 11 in stage IV were treated in the Department of Radiation Oncology, University Hospital of Muenster, Germany from 2004 to 2016. Radiotherapy (RT), as well as additional chemoimmunotherapy were analyzed with a median follow-up of 87.6 months. Ultrasound (US), CT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…However, it is known that lymphoma in general, and especially low-grade lymphoma such as MZBCL or FL, is highly responsive to RT alone [20,21,[27][28][29]. This turned out to be true for parenchymal LG-PCNSL in the patient cohort presented here and is corroborated by the literature [11][12][13][14]16,23,30].…”
Section: Discussionsupporting
confidence: 82%
“…However, it is known that lymphoma in general, and especially low-grade lymphoma such as MZBCL or FL, is highly responsive to RT alone [20,21,[27][28][29]. This turned out to be true for parenchymal LG-PCNSL in the patient cohort presented here and is corroborated by the literature [11][12][13][14]16,23,30].…”
Section: Discussionsupporting
confidence: 82%
“…Their study showed that involved field radiation combined with immunotherapy is a valuable therapeutic tool for the treatment of early-stage nodal and extranodal follicular lymphomas. 18 F-FDG-PET-CT is an optimal approach for staging, especially in early-stage follicular lymphomas, which enables the identification of patients with excellent prognosis by radiotherapy [ 4 ].…”
mentioning
confidence: 99%